PEMETAAN SEBARAN KASUS GIZI BURUK BALITA UMUR 0-59 BULAN DI KOTA LHOKSEUMAWE TAHUN 2012 - risa amalia amalia; Erna Mutiara; Jumirah . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Severe malnutrition at this time is a matter of special concern in the city of Lhokseumawe, because it may cause a lost generation. Data of malnutrition cases can be presented spatially and can be drawn in a map by using Quantum GIS Software.This research aimed to make a map of the distribution of under five malnutrition cases in the city of Lhokseumawe in 2012. This is a descriptive research. The population were all of under five malnutrition cases and registered at Lhokseumawe Health Office as many as 43 cases in 2012, and all of them were selected as samples. The result showed that out of 43 under five malnutrition cases in Lhokseumawe city, the 15 cases (34.88%) were found in Banda Sakti subdistrict and they were near the beach, the cases with clinical symptom were 15 cases, the cases without clinical symptom were 2 cases (4.65%) and they were spread out the hill and on the side of the road, 8 cases (18.60%) were in radius < 1 km from their houses to health center, 12 cases (27.91%) were in radius < 1 km to the hospital, and 1 case (2.33%) died in radius < 1 km to the hospital. By using Quantum GIS software through Geographic Information System (GIS), it would be easy for Health Office of Lhokseumawe City and health centers in making intervention to malnutrition countermeasure.Keywords: Malnutrition, Under Five, Mapping, Quantum GIS, Geographic Information System